Easy steps to safe swimming a swimming handbook - McAllister, Evelyn Ditton (South Brunswick A. S. Barnes, 1973)
Includes directions for the basic swimming strokes, first-aid techniques, safety rules, an introduction to scuba diving, and a special section on ocean swimming.
Includes index.
Keywords: Swimming